Technology Integration in Islamic Education: Policy Framework and Adoption Challenges - Sholeh, Muh Ibnu (Journal of Modern Islamic Studies and Civilization, 2023)
This study aims to find how the strategy for implementing technology integration in Islamic education is effective and how to overcome the challenges of adopting technology integration in Islamic education. The method used in this study is a descriptive qualitative approach. Qualitative descriptive research is research that produces descriptive data in the form of written or spoken words from people and observable behavior. The type of research used in this research is literature study. Data analysis was carried out using a descriptive analysis, by looking for patterns and finding themes that emerged from the materials collected. This study was analyzed by the stages of data collection, data presentation, data condensation and drawing conclusions. The results of the study show that the strategy for implementing technology integration in Islamic education is through improving technology infrastructure, training and professional development for teachers and education managers, preparing relevant digital Islamic content, and a technology-based curriculum approach. Addressing the challenges of adopting technology integration in Islamic education through increasing the accessibility of technology, developing technology training and certification programs for teachers, diversifying funding sources for technology integration, and a flexible approach to curriculum development and evaluation